2019
DOI: 10.1523/jneurosci.1451-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in the Cerebral Cortex Functional Organization of Healthy Elderly

Abstract: Healthy aging is accompanied by disruptions in the functional modular organization of the human brain. Cross-sectional studies have shown age-related reductions in the functional segregation and distinctiveness of brain networks. However, less is known about the longitudinal changes in brain functional modular organization and their associations with aging-related cognitive decline. We examined age-and aging-related changes in functional architecture of the cerebral cortex using a dataset comprising a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
105
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 86 publications
12
105
1
3
Order By: Relevance
“…Community detection at both stages was performed using a range of γ parameters from 1 to 6 (resolution parameter γ determines the number of communities detected). We reported findings using individual-level γ = 3 and group-level γ = 2, as the brain network communities derived from the HC group with these two parameters best reflected the normative network organizations described in previous literature [ 24 , 26 , 115 ].…”
Section: Methodsmentioning
confidence: 61%
“…Community detection at both stages was performed using a range of γ parameters from 1 to 6 (resolution parameter γ determines the number of communities detected). We reported findings using individual-level γ = 3 and group-level γ = 2, as the brain network communities derived from the HC group with these two parameters best reflected the normative network organizations described in previous literature [ 24 , 26 , 115 ].…”
Section: Methodsmentioning
confidence: 61%
“…Therefore, we proposed that older adults establish a compensatory mechanism for processing high-level cognitive semantic audio-visual stimuli, and the enhanced AVI effect was an adaptation of the ageing brain to compensate for unimodal functional decline. Furthermore, accompanying sensory process declines, reduced differentiation abilities, and regional process specificity of the ageing brain have also been extensively reported (Chong et al, 2019;Grady, 2012). Wang et al (2018) investigated age-related functional connectivity in audio-visual temporal asynchrony integration tasks, and their results illustrated that the functional connectivity and network efficiencies of older adults revealed higher global and local efficiencies in both the theta and alpha bands.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we proposed that older adults establish a compensatory mechanism for processing high-level cognitive semantic audio-visual stimuli, and the enhanced AVI effect was an adaptation of the ageing brain to compensate for unimodal functional decline. Furthermore, accompanying sensory process declines, reduced differentiation abilities, and regional process specificity of the ageing brain have also been extensively reported ( Chong et al., 2019 ; Grady, 2012 ). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that all of the patients in Phenotype 4 are undergoing AD-like changes, it is more likely that this pattern is in fact representative of baseline age-related cognitive changes. A recent study comparing young versus older adult connectomes showed declines in the functionality of this same dorsal prefrontal-attention axis even in healthy elderly patients while executive, orientation, visuospatial, and language areas were spared 27 . The prevalence of Phenotype 4 suggests that it is a common degenerative pathway in all of this study's patients, including the cognitively normal ones.…”
Section: Discussionmentioning
confidence: 92%